COASTAL VULNERABILITY ASSESMENT OF TOURISM AREA AND MANAGEMENT STRATEGY FOR SUSTAINABLE ENVIRONMENTAL RESILIENCE: CASE OF MANDEH COAST, WEST SUMATERA - GEMILANG, WISNU ARYA; WISHA, ULUNG JANTAMA; DHIAUDDIN, RUZANA (Badan Informasi Geospasial, 2020)
Mandeh area located in Pesisir Selatan Regency is a beautiful coastal bay that is why the local governments focus on its tourism development. However, this coastal bay region is potentially affected by the disaster, thus sustainable coastal management is essential to be applied. To assess the vulnerability of Mandeh Bay, CVI method and the Smartline mapping approach are utilized by applying several physical parameters. The aforementioned parameters encompassed beach materials, wave exposure, hinterland formation, berm features, beach-face features, coastline changes, and land-use patterns. The results show that several regions within Mandeh Bay categorized into very low vulnerability 10%, low vulnerability 27%, moderate vulnerability 18%, high vulnerability 31%, and very high vulnerability 14%, respectively. Most of the northern coastal areas of the XI Koto Tarusan Sub-District predominated by the high vulnerability. Therefore, the development of coastal building in the forms of hard and soft structures, as well as the establishment of regional regulation regarding coastal zone utilization to prevent further environmental degradations and coastal hazards are necessary as a part of coastal management of this study area.